Forc Analysis of Ni(Sio 2 Nanogranular Film in the Blocked Regime - Casagrande-Denardin, J (2012)
In this work the magnetic and structural properties of granular Ni(SiO 2) films are studied by means of FORCs diagrams and microscopy. Transmission electron microscopy images show that the sample is composed of a fine dispersion of Ni nanoparticles with 3.7 nm in average sizes. Magnetic measurements as function of temperature show that the nanoparticles are superparamagnetic at room temperature and are blocked at 5 K. The FORCs diagrams obtained below the blocking temperature allow us to determine the average size of the nanoparticles and the distribution of sizes in a very good agreement with TEM images. © 2012 Elsevier B.V. All rights reserved.